2007
DOI: 10.1007/s10964-007-9217-z
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Cultural Dissonance, Parent–Child Conflict and Bonding, and Youth Problem Behaviors among Vietnamese and Cambodian Immigrant Families

Abstract: Intergenerational cultural dissonance (ICD)-a clash between parents and children over cultural values-is a frequent issue for Asian American youth. Using longitudinal data from the Cross Cultural Families Project, this study examines the mechanisms by which ICD contributes to problem behaviors, including whether ICD predicts parent-child conflict, whether parent-child conflict then has a direct effect on youth problem behavior, and whether positive bonding with parents mediates the effects of such conflict on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(202 citation statements)
references
References 49 publications
4
196
1
1
Order By: Relevance
“…Within the general population, most intergenerational conflicts seem to occur owing to the developmental processes that manifest over mundane issues, such as doing chores and one's appearance, which may not necessarily have significant detrimental impact on a child's mental health (Steinberg, 2001). However, the term intergenerational conflict in immigrant families has a distinctive feature that describes the far greater condition of relational conflict due to the cultural and value dissonance between immigrant parents and their children (Choi, He, & Harachi, 2008). As a matter of fact, over the past two decades, extensive research has shown the negative effects of intergenerational conflict on the mental health of Asian American families in general (Chung, 2001;Lee, 2003;Lee, Cho, Kim, & Ngo, 2000;Ying & Tracy, 2004) and in SEA families, including Vietnamese (Dinh, Sarason, & Sarason, 1994;Kibria, 1993;Ying & Han, 2007;Zhou & Bankston, 1998).…”
Section: Depression Factors In Vietnamese American Studentsmentioning
confidence: 99%
“…Within the general population, most intergenerational conflicts seem to occur owing to the developmental processes that manifest over mundane issues, such as doing chores and one's appearance, which may not necessarily have significant detrimental impact on a child's mental health (Steinberg, 2001). However, the term intergenerational conflict in immigrant families has a distinctive feature that describes the far greater condition of relational conflict due to the cultural and value dissonance between immigrant parents and their children (Choi, He, & Harachi, 2008). As a matter of fact, over the past two decades, extensive research has shown the negative effects of intergenerational conflict on the mental health of Asian American families in general (Chung, 2001;Lee, 2003;Lee, Cho, Kim, & Ngo, 2000;Ying & Tracy, 2004) and in SEA families, including Vietnamese (Dinh, Sarason, & Sarason, 1994;Kibria, 1993;Ying & Han, 2007;Zhou & Bankston, 1998).…”
Section: Depression Factors In Vietnamese American Studentsmentioning
confidence: 99%
“…Many studies have used the term 'Asian American' to refer to the larger group of immigrants from Asian countries. However, despite the widespread use of the pan-ethnic term "Asian" in the literature, there are distinctions between Asian sub-groups (Choi et al, 2008;Ishii-Kuntz, 2000). Future studies should explore unique differences between families from various Asian countries to further understand the factors that play unique roles in family dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have compared AA youth with their European American counterparts have found that AA youth experience higher rates of intergenerational conflict that often stems from differences in acculturation between parents and their children (Greenberger & Chen, 1996;Farver et al, 2007;Lee & Liu, 2001). Moreover, studies have linked cultural dissonance between AA youth and their parents to heightened distress among these youth (Choi et al, 2008;Greenberger & Chen, 1996;Hwang et al, 2010;Kwak, 2003;Lee & Liu, 2001;Qin, 2008;Ying & Han, 2007).…”
Section: Immigration-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…also states that children who are attached to their parents are more likely to spend time in the presence of their parents. Further, troubled parent-child relationships, such as relationships characterized by many parentchild conflicts, may result in a variety of negative consequences, including the weakening of positive parent-child bonding, and adolescent offending (Choi et al 2008). In the original statement of social bonding theory, attachments between parent and child, and their correlation with offending, were proposed to be universal with respect to gender .…”
Section: Introductionmentioning
confidence: 99%